PENGOLAHAN DAUN TALAS BENENG SEBAGAI ALTERNATIF PENGGANTI DAUN TEMBAKAU UNTUK BAHAN BAKU PRODUK ROKOK HERBAL: PENDAMPINGAN UMKM PADA POKTAN “TANI BAKO“ - Sunardi Sunardi; Basuki Rakhim Setya Permana (Batara Wisnu : Indonesian Journal of Community Services, 2023)
This research aims to evaluate the potential of processing beneng taro leaves as an alternative to replace tobacco leaves in herbal cigarette production. The primary focus of the study is on supporting Micro, Small, and Medium Enterprises (MSMEs) in the "Tani Bako" farmer group. The research methods include the collection of beneng taro leaves, chemical composition analysis, and testing of herbal cigarette products from the processing. The expected outcomes of this research include contributing to the diversification of raw materials for herbal cigarettes, enhancing the well-being of MSMEs, and reducing dependence on conventional tobacco leaves. The study supports the sustainability of local agricultural efforts and encourages the adoption of herbal cigarette practices as an innovative step in tobacco product development